Effects of Crude Plant Extracts from Five Parts of Melia azedarach on Tribolium confusum - Omar, Muzafar K.; Muhammad, Hanaa A.; Mirkhan, Sawan M. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2023)
Tribolium confusum is one of the most common pests of many commodities, especially cereals and their products. These pests are known for being the most destructive insect pests attacking and infesting stored flour and grain in soil, warehouses, grocery stores, and homes. Therefore, this study aims to control these pests with an environmentally friendly, healthier, and cost-effective pesticide instead of the common artificial chemicals to practice the current management of cereal storage pest control in the Kurdistan Region of Iraq. For this to be achieved, the toxicity effect of crude plant extracts from five different parts of Melia azedarach in tap water with concentrations of 50%, 60%, 70%, 80%, and 90% at different times (2, 4, 6, 8, and 10 h) against stored-product insect was tested. The toxicity effect of these extracts varied based on the crude plant part extracts, concentrations, and exposure period according to the SAS system investigation on the mortality rate of T. confusum adults (Duncan test). The extracts’ compatibility with treated adults of T. confusum in the clear petri dish was noted. Besides, the number of dead adults was measured by loss of motion.